Adaptive Cell-Mediated Immunity in the Mammary Gland of Dairy Ruminants - Rainard, Pascal; Foucras, Gilles; Martins, Rodrigo P. (Frontiers in Veterinary Science, 2022)
Historically, attempts to enhance immunity to mammary gland (MG) infection have primarily focused on the induction of antibodies to bacterial pathogens. Early on, it appeared that the adaptive immunity of the MG of dairy ruminants, unlike that of laboratory rodents, pigs or humans, is not linked to the gut-associated mucosal immune system. The MG of ruminants does not express the vascular addressins of the common mucosal lymphoid system. The progressive realization that cell-mediated immunity is of major importance for the control of mastitis prompted investigations on the immune cells that populate the MG. As an immune inductive site, the MG is equipped with antigen-presenting cells, associated to the epithelium lining, capable of sampling and handling luminal antigens. The responses to immunization are both local and systemic, and most efficiently induced before or between lactations. Most lymphocytes are distributed diffusely in the MG connective tissue and epithelium, but inducible tertiary lymphoid structures can be elicited by chronic infections. Highest immune responses and best protection result from the combination of systemic immunization followed by a local booster. An antigen-specific mammary neutrophilic response that is driven by resident memory T lymphocytes producing IL-17 cytokines is induced upon immunization by either route. Although most lymphocytes in milk and tissue from healthy or inflamed glands have a phenotype of effector or memory cells, we have very little knowledge of the functions of the mammary resident lymphocytes, in particular the CD8 T cells that are in close association with the mammary epithelium. The cytokines IL-17A and IL-17F along with IFN-γ strengthen the defenses of the epithelial barrier. Gaps in knowledge about cell-mediated immunity in the MG hamper progress in the rational design of effective vaccines mastitis. More research should be devoted to resident memory T lymphocytes in the MG and ways to populate the MG with those that protect against mammary infections.